Biochemical characterization of recombinant cinnamoyl CoA reductase 1 (Ll-CCRH1) from Leucaena leucocephala - Sonawane, Prashant; Vishwakarma, Rishi Kishore; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2013)
Recombinant cinnamoyl CoA reductase 1 (Ll-CCRH1) protein from Leucaena leucocephala was overexpressed in Escherichia coli BL21 (DE3) strain and purified to apparent homogeneity. Optimum pH for forward and reverse reaction was found to be 6.5 and 7.8 respectively. The enzyme was most stable around pH 6.5 at 25 degrees C for 90 min. The enzyme showed k(cat)/k(m) for feruloyl, caffeoyl, sinapoyl, coumaroyl CoA, coniferaldehyde and sinapaldehyde as 4.6, 2.4, 2.3, 1.7, 1.9 and 1.2 (x10(6) M-1 s(-1)), respectively, indicating affinity of enzyme for feruloyl CoA over other substrates and preference of reduction reaction over oxidation. Activation energy, E-a for various substrates was found to be in the range of 20-50 kJ/mol. Involvement of probable carboxylate ion, histidine, lysine or tyrosine at the active site of enzyme was predicted by pH activity profile. SAXS studies of protein showed radius 3.04 nm and volume 49.25 nm(3) with oblate ellipsoid shape. Finally, metal ion inhibition studies revealed that Ll-CCRH1 is a metal independent enzyme. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Activation energy; Cinnamoyl CoA esters; Cinnamoyl CoA reductase 1; SAXS; stability